Strategy Of The Ministry Of Pariwista Timor-Leste In The Development Of Community Based Pariwista - Bernabe De Lima Araujo (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The Timor-Leste government's strategy in building a community-based pariwista sector “this study aims to find out and analyze the Timor-Leste government's strategy in building the community tourism sector, and what phenomena the Government faces in building a community-based tourism sector, by describing the results of the local government's strategy in building a community-based tourism sector. Based on data and information, the ministry of tourism has always tried to build a pariwista sector for the nation and the State, despite the many obstacles or obstacles faced by the ministry, but the government through the Ministry of Tourism of Timor-Leste remains steadfast in the combination or Matadalan" Planu Estrategi Dezemvolimnetu Nasional 2011-2030 in order to build Timor-Leste based on the vision and mission implemented in the State and building its society in accordance with the development and development of the community through community visits in various aspects needed individually and in groups, as well as the State with the State, especially in the pariwista sector. he construction of pariwista presented by various respondents in the interpretation results, many respondents gave various inputs and conclusions that, the Government needs to be in harmony with the community in building pariwista because the tourism sector will provide contribution to the nation and the State. The government through the Timor-Leste pariwista ministry needs to promote local and national pariwista places throughout the world. The cooperation of the government and the local community is a habit in building a pariwista tail in the future, The purpose of building a community-based pariwista, is one of the most important things among the community, meaning that the community can bathe early in various sectors of their living needs, Physical and non-physical development in the pariwista sector needs to be considered in a sustainable manner, so that parawisatwan do not feel hesitant in ending to the tourism place. The researcher recommended to the government in this case the department of the Timor-Leste pariwisat ministry that, the Government needs to develop tourism objects in Timor-Leste, with better facilities. Security officers need to be placed also in tourism places, the Ministry of Tourism in Timor-Leste needs to support small industries in the city and in areas with pariwista potesial to produce local materials, gelan, tais Timor and other souvenirs to be marketed in tourist attractions, It is necessary to have a law regulating to give punishment to people who litter in tourist attractions, It is necessary to place health workers who can provide services to tourists in tourist attractions when in need on an emergency basis, There is good cooperation between the ministry of tourism and with relevant institutions and the security of existing civil to take care of existing tourist sites, the Government needs to provide scholarships to Timor - Leste castles to study about tourism programs in other places, thus it can help the government to build tourist attractions in cities and remote areas in general in Timor - Leste.